The role of leader-member exchange on subjective career success among teachers - Dewi, Yolanda Kartika; Ingarianti, Tri Muji; Andriany, Devina (Universitas Muhammadiyah Surakarta, 2022)
Abstract. Teacher’s subjective career success can be evaluated from their career satisfaction. When evaluating the career, the teachers feels a sense of comfort in their work environment and career, that arises from the support provided by the leader to the teacher. The purpose of this study was to determine whether there is a role for leader-member exchange on subjective career success for teachers. Participants in this study were 320 teachers. The method used in this study used quantitative methods. The instruments used in this research are Leader-Member Exchange Multidimensionality (LMX-MDM) and the Subjective Career Success Inventory (SCSI) scale. This study used two data analyzes, the first using a simple linear regression test with a total score of significant results (b= 0.356; p 0.001). Second, multiple linear regression tests with per-dimensional analysis obtain a significant result on the contribution dimension to the recognition dimension and the affect dimension to the overall dimensions of subjective career success (b=0.146 – 0.282; p 0.001). The results of this study can be used as a reference in the development of psychology related to leader-member exchange and subjective career success.Keywords: leader-member exchange; subjective career success; teacher